POVERTY AND DEVELOPMENT IN NIGERIA: TRAILING THE MDGS? - Omideyi, Adekunbi Kehinde (African Journal of Infectious Diseases (AJID), 2007)
Poverty levels in the developing world, especially Sub-Saharan Africa still pose major challenges to overall development in the continent and globally, against the backdrop of the millennium development goals. A critical appraisal of poverty and development theories suggests that as long as individuals and communities are caught in poverty traps (in the form of low resources, low physical and human capital), exclusions from global markets and government and market failures they cannot enjoy the economic development experienced in high income, developed countries. The MDGs were developed in good faith to assist in reducing global economic development disparities; however, an assessment of the current status of African countries reveals a trend whereby it is highly unlikely that any of the targets set by the goals will be met by 2015. Goal 4 - the reduction of infant mortality rates - which would have been met, has been threatened by civil disturbances and increasing incidence of HIV/AIDS. Within Nigeria, where 50% live below the poverty line, the poverty situation is exacerbated by inequality in incomes, in assets (education and health status), in control over public resources and in access to essential services, coupled with high levels of insecurity. Growth strategies for reducing poverty levels in Sub-Saharan countries, and Nigeria in particular, must be pro-poor. Such strategies must eliminate discrimination against rural and agricultural development; invest in human capital (education and health); improve household consumption levels to reduce deprivation of basic needs by vulnerable members, particularly children, the widowed and the aged; provide access to markets and public infrastructure and facilitate the creation of new jobs. Ongoing economic and structural reforms in the country must be maintained on a sustained level that will permit poverty reduction and better quality of life.